GLClick: Interactive Segmentation Combining Global and Local Features - Jiaying Tang; Hongyuan Wang; Zongyuan Ding; Zihao Xin (Applied Sciences)
Convolutional neural networks (CNNs) are the backbone of most modern interactive segmentation algorithms. However, the limited receptive field of CNNs restricts their ability to capture long-range semantic relationships. Recently, transformers have gained significant attention for their capacity to capture long-range dependencies. Nevertheless, CNNs still outperform Transformer in extracting local information. An effective interactive segmentation algorithm should accurately capture fine-grained local details alongside global semantic relationships. Therefore, we propose GLClick, a global–local click-based interactive image segmentation model that integrates local and global information through a novel fusion mechanism. We design an efficient global–local feature fusion module (GLFM) that integrates fine-grained features from various layers of ResNet50 with those from the Transformer feature pyramid. This approach maintains ResNet50’s ability to extract local features while effectively leveraging the Transformer to capture global context. Additionally, we enhance the multi-layer perceptron (MLP) to improve performance. Extensive experiments on diverse benchmark datasets demonstrate significant improvements in interactive image segmentation, confirming the effectiveness of our approach. Moreover, we conduct experiments on medical image datasets, further illustrating the model’s versatility and effectiveness across different domains.